(untitled) (Transport systems and technologies, 2022)
The article is devoted to the issue of finding effective ways to restore the sector of transport and logistics activities of the country in the postwar period, which is currently relevant for Ukraine. The state of international transportation during the war is analyzed. It is established that the process of restoration of the transport and logistics sector in the country is already underway and consists of a number of measures in the field of customs, logistics and transports. The experience of restoring the transport sector in European countries as part of the national critical infrastructure is considered. It is determined that one of the main conditions for effective economic recovery is international support. The key programs, diplomatic and legal documents that formed the basis for the creation of international support for Ukraine in economic recovery in general and the transport sector in particular are considered. The basic directions in which the action of the specified support for transport and logistics activity is directed are established.